Pflege im Spannungsfeld von Angebot und Nachfrage - Tobias Hackmann; Stefan Moog (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2008)
Currently nearly half of people eligible for long-term care benefits in Germany are receiving informal care by family members. Accounting for the ongoing ageing process of society, an increasing labour participation rate of women and a rising part of old aged living alone, the question is if informal care can maintain its dominant role. Due to the doubling of persons in need of care until 2050 and low fertility rates, we project a decreasing share of informal care over the next decades. Thus, (more expensive) formal care will receive more importance leading to an increasing demand of professional nursing staff.
Keywords: I12; J14; J50; 330; Informelle Pflege; Formelle Pflege; Heimsog-Effekt; Demografie; Pflegedienst; Heim; Pflegeberufe; Alternde Bevölkerung; Deutschland